FACE-NEGOTIATION ANTARA KOMUNITAS SUPORTER TIM SEPAK BOLA YOGYAKARTA BCS DAN BRAJAMUSTI DALAM KOMUNIKASI ANTARPRIBADI DI LUAR MATCH - Agusta, Rivga (Jurnal Ilmu Komunikasi AKRAB, 2018)
AbstractThe fanaticism of supporters of the pride of the football team in each region often causes trouble outside the ?field?. This kind of fanaticism also occurs between two supporters of the football team in Yogyakarta, namely the Brigata Curva Sud (BCS) community and Brayat Jogja Utama Sejati (Brajamusti). Although they have long experienced